PENGARUH INTEGRITAS, KOMITMEN ORGANISASI DAN KECERDASAN ADVERSITY TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI WILAYAH BALI - Ni Kadek Sugiartini; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2021)
Public accountants are professionals who provide services to the general public, especially in the field of auditl of financial reports, which play a role in improving the quality of financial information. This study aims to determine the effect of integrity, organizational commitment and adversity intelligence on audit quality. This research was conducted in the Public Accountants Office in the Province of Balil which was registered at the Indonesian Institute of Public Accountants (IAPI), totaling eleven KAPl with a population of 92 auditors. The method used in this study is purposive sampling with an auditor's criterion who has had audit experience â‰¥ 1 year and an auditor who has a minimum educational history of Stratal 1 (S1) 1, so the number of samples in this study is 63 auditors. The data collection method was carried out by a survey method using the questionnaire technique which was measured using a likertl scale. The results of this study show that integrity has a positive effect on audit quality with a significant value of 0l, 001 <0l, 05l. Organizational commitment to results has a positive effect on audit qualityl with a significant value of 0.1003 <0.051. Adversity intelligence has a positive effect on audit qualityl with a significant value of 0l, 017 <0l, 05l. This hall indicates that the higher the variable, it means the higher the audit quality produced by the auditor.